Molecular Pathways in Peritoneal Mesothelioma: A Minireview of New Insights - Fortarezza, Francesco; Pezzuto, Federica; Marzullo, Andrea; Cavone, Domenica; Romano, Daniele Egidio; d’Amati, Antonio; Serio, Gabriella; Vimercati, Luigi (Frontiers in Oncology, 2022)
Mesothelioma is a rare malignant neoplasm with poor survival. It mainly affects the pleura (90%) but can arise in all serous cavities: peritoneum (5-10%), pericardium and tunica vaginalis testis (<1%). The onset of pleural mesothelioma is strictly related to asbestos exposure with a long latency time. The causal link with asbestos has also been suggested for peritoneal mesothelioma, while the importance of exposure in the onset of pericardial and tunica vaginalis testis mesotheliomas is not well known. Mesothelioma remains an aggressive and fatal disease with a five-year mortality rate higher than 95%. However, new therapeutic approaches based on molecular-targeted and immunomodulatory therapies are being explored but have conflicting results. In this context, the identification of critical targets appears mandatory. Awareness of the molecular and physiological changes leading to the neoplastic degeneration of mesothelial cells and the identification of gene mutations, epigenetic alterations, gene expression profiles and altered pathways could be helpful for selecting targetable mechanisms and molecules. In this review, we aimed to report recent research in the last 20 years focusing on the molecular pathways and prognostic factors in peritoneal mesothelioma and their possible diagnostic and therapeutic implications.